On the fallacy of single trials: a proposal to reduce variability in running shoe research - Beltrami, F. G.; Baumann, G.-A.; Biedermann, K.; Spengler, C. M. (Sports Medicine, 2025)
Advanced footwear technology (AFT) [1] provides substantial improvements in running economy [2] and performance [3], but there is still much debate about the relative contribution of the different shoe properties involved, including shoe mass [4], compliance [5], resilience [6], and longitudinal bending stiffness [7]. As a result, there has been a resurgence of research on the topic.